Brain Edema XV - Katayama, Yoichi; Maeda, Takeshi; Kuroiwa, Toshihiko; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2013)
More than 60 papers written by internationally recognized experts cover the broad spectrum of brain edema. The main topics treated are: ischemia & hemorrhage, trauma (experimental and clinical), cerebral hemorrhage, tumor, hydrocephlaus & intracranial pressure (ICP), neuromonitoring & neuroimaging, treatments, blood brain barrier, and miscellaneous.
Historical review -- Ischemia & hemorrhage -- Trauma (experimental) -- Trauma (clinical) -- Cerebral Hemorrhage -- Tumor -- Hydrocephalus & intracranial pressure (ICP) -- Neuromonitoring & neuroimaging -- Treatments -- Blood brain barrier, miscellaneous.
Keywords: Medicine; Neurosurgery; Medicine & Public Health; Neurosurgery